Phosphorus in smallholder farming systems of sub-Saharan Africa: implications for agricultural intensification - Nziguheba, Generose; Zingore, Shamie; Kihara, Job Maguta; Merckx, Roel; Njoroge, Samuel M.; Vandamme, Elke; Vanlauwe, Bernard (Springer, 2016)
Current efforts in combating food insecurity in sub-Saharan Africa (SSA) focus on agricultural intensification. Given the high soil nutrient depletions, replenishing soil fertility is a major component of such efforts. One of the key nutrients limiting crop production is phosphorus (P). Overcoming P deficiency in smallholder farming in SSA faces many challenges, mainly because the causes of P deficiencies vary, and viable options to replenish soil P have limitations. In some areas, P deficiency is associated with a low P reserve, while in others, it results from a high soil P-adsorption capacity. Numerous studies have focused on developing approaches and strategies with potential to replenish soil P or improve its availability to crops. This paper highlights approaches and strategies that have been studied, including the use of soluble P fertilizers, phosphate rocks and organic resources. The contribution of soluble P fertilizers is mainly limited by their high cost, while most phosphate rocks are not mined. Replenishing P through organic resources is constrained by their often low P content and inadequate availability in smallholder farms. Optimizing the P use efficiency appears as the most plausible target pending an increased accessibility of P sources to farmers. Practices towards this optimization include strategic crop sequences and P allocation to crops, use of P-efficient genotypes, and targeting the residual P. Research is needed towards gaps in understanding processes governing benefits associated with these practices. Since P replenishment is fertilizer dependent, greater attention is required in enhancing the accessibility of P fertilizers to smallholder farmers.